1982
DOI: 10.1017/s0251107x00004491
|View full text |Cite
|
Sign up to set email alerts
|

Solar Activity

Abstract: This report summarizes research on solar activity over an almost three-year period from January 1, 1979, till the end of June 1981. In preparing this report we respected the advice of the I.A.U. Executive Committee to cover the highlights of work carried out in the field of solar physics relevant to our Commission, and avoiding double work. Only a limited space was made available for our Commission. Given this restraint we tried to produce a comprehensive review. With great pleasure I appreciate the excellent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 113 publications
2
3
0
Order By: Relevance
“…In skimming over Our magnetic and Doppler velocity maps of solar active regions, we noticed that the growth, renewal or decrease of spot-forming activity in active regions is locally related to the singularities of their magnetic field topologies (inclusions of opposite polarities, or just the boundary of both polarities, usually with large magnetic gradients) which develop very rapidly, as we have already demonstrated earlier (Bumba 1988). These magnetic singularities are accompanied by a specific situation in the distribution of line-of-sight motions, demonstrating that also the velocity field is strongly disturbed, or rather very active, in such locations.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…In skimming over Our magnetic and Doppler velocity maps of solar active regions, we noticed that the growth, renewal or decrease of spot-forming activity in active regions is locally related to the singularities of their magnetic field topologies (inclusions of opposite polarities, or just the boundary of both polarities, usually with large magnetic gradients) which develop very rapidly, as we have already demonstrated earlier (Bumba 1988). These magnetic singularities are accompanied by a specific situation in the distribution of line-of-sight motions, demonstrating that also the velocity field is strongly disturbed, or rather very active, in such locations.…”
Section: Introductionsupporting
confidence: 63%
“…As we have demonstrated earlier (Bumba 1988;Bumba et al 1993 and the new magnetic flux develops in the place, where at least opposite polarity magnetic fields malie contact and certain magnetic gradient exists. The magnetic situation can be more complicated, gradients large, the developing activity is then also very large.…”
Section: New Activity Is Related To Both the Magnetic And Motion Fielsupporting
confidence: 51%
“…The persistence of the supergranulation and mesogranulation pattern during the formation of the BMR brings back memories to the observations reported many years ago by Bumba (1963Bumba ( , 1967 and Bumba & Howard (1965). According to these researchers, the growing magnetic fields of BMRs do not break down the pre-existing convectivevelocity field but come from below "seeping" through the network of convection cells.…”
Section: Discussionmentioning
confidence: 74%
“…The effects of the solar cycle on meteor rates were first studied by Bumba (1949), who reviewed visual meteor records from 1844 to 1943, and found that the rates peaked 5 years after maximum solar activity, and were lowest two years after solar minimum. However, it was not possible to rule out E-mail: margaret.campbell@uwo.ca changes in cloud cover, for example, and he found similar variations in the number of comets seen and meteorite falls and finds, all of which seem unlikely to be affected by atmospheric variations in the same way as meteors.…”
Section: Solar Activity Effects On Meteor Ratesmentioning
confidence: 99%